Cytotoxicity of curcumin against CD44± prostate cancer cells: Roles of miR-383 and miR-708 - Reza Panahizadeh; Mohammad Amin Vatankhah; Farhad Jeddi; AmirAhmad Arabzadeh; Kazem Nejati-Koshki; Ramin Salimnejad; Nowruz Najafzadeh (Mashhad University of Medical Sciences, 2023)
Objective: Cancer stem cells (CSCs) remaining in the tumor tissues after applying treatments may cause recurrence or metastasis of prostate cancer (PC). Curcumin has the promising potential to target CSCs. Here, we aim to evaluate the cytotoxic effects of curcumin on the expression of miR-383-5p and miR-708-5p and their target genes in CD44+ CSCs and CD44- non-CSCs isolated from the PC3 prostate cancer cell line.Materials and Methods: We used MTT assay to determine the optimal cytotoxic dose of curcumin on CD44± PC cells. Then, we assessed nuclear morphological changes using DAPi staining. We used Annexin V-FITC/PI to quantify apoptotic cell death. qRT-PCR was also used to detect miRNA and gene expression levels after curcumin treatment.Results: Curcumin significantly enhanced the apoptosis in both CD44- and CD44+ PC cells in a dose-dependent manner (p < 0.05). The cytotoxicity of curcumin against CD44- cells (IC50  40.30±2.32 μM) was found to be greater than that against CD44+ cells (IC50  83.31±2.91 μM). Also, curcumin promoted miR-383-5p and miR-708-5p overexpression while downregulating their target genes LDHA, PRDX3, and RAP1B, LSD1, respectively.Conclusion: Our findings indicate that curcumin, by promoting the expression of tumor suppressors, miR-383-5p and miR-708-5p, and inhibiting their target genes, induced its cytotoxicity against CD44± PC cells. We trust that curcumin could be established as a promising adjuvant therapy to current PC treatment options following more research in clinical settings.